The effects of fear appeal message repetition on perceived threat, perceived efficacy, and behavioral intention in the extended parallel process model - Shi, Jingyuan (Jolie) (2015)
This study examined the effect of moderately repeated exposure (three times) to a fear appeal message on the Extended Parallel Processing Model (EPPM) variables of threat, efficacy, and behavioral intentions for the recommended behaviors in the message, as well as the proportions of systematic and message-related thoughts generated after each message exposure. The results showed that after repeated exposure to a fear appeal message about preventing melanoma, perceived threat in terms of susceptibility and perceived efficacy in terms of response efficacy significantly increased. The behavioral intentions of all recommended behaviors did not change after repeated exposure to the message. However, after the second exposure the proportions of both systematic and all message-related thoughts (relative to total thoughts) significantly decreased while the proportion of heuristic thoughts significantly increased, and this pattern held after the third exposure. The findings demonstrated that the predictions in the EPPM are likely to be operative after three exposures to a persuasive message.